Practical Aspects of Consideration of Disputes Associated with the Education of Children in a Juvenile Court - MUTUBAYEVA, Dinara; KOZHAKHMETOV, Galym; BOZHKARAULY, Altai; RUSTEMBEKOVA, Dinara (Journal of Advanced Research in Law and Economics; Vol 9 No 3(33) (2018): JARLE, Volume IX, Issue 3(33), Summer 2018DO - 10.14505//jarle.v9 3(33).32, 2018)
In accordance with Article 27 of the Constitution of the Republic of Kazakhstan of August 30, 1995 (hereinafter - the Constitution), marriage and family, motherhood, fatherhood and childhood are under state protection, which is a fundamental point in the legal regulation of family relations. Respect for human rights begins with respect for the rights of the child. The lack of due attention on the part of the state to the problem of children can be qualified as non-compliance by Kazakhstan with certain provisions of the Universal Declaration of Human Rights and the Convention on the Rights of the Child (hereinafter referred to as the Convention). The creation of juvenile justice in Kazakhstan is becoming more and more relevant, although the term ‘justice ensuring the rights, freedoms and legitimate interests of minors’ is more understandable and precise.